An image [1983] - Farocki, Harun (Chicago : Facets Video, 2006)
Shot in four days (July 19-22, 1983) at Playboy's photography studio in Munich, the film begins with the building of the set and follows through to the dismantling of the set at the end of the job. Farocki includes all phases of the photo shoot and shows the participation of the many people involved in making one photo. Though the Playboy photographer instructs the model to "give us your usual saucy look", Farocki strips the glamour and allure from the subject by focusing on the labor and orchestration behind it.
German dialogue with English subtitles.
film
Keywords: Farocki, Harun